LESSON LEARNED FROM PILOTING COLLABORATIVE ELECTIVE POSTING FOR MEDICAL STUDENTS BASED ON LOCAL WISDOM - Mustika, Rita; Felaza, Estivana; Fadhilla, Maulida Rohmatul (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: The COVID-19 Pandemic urges medical education to adjust the learning process, one of which is to become more efficient. Sharing resources is one of the adjustments that could be applied, and the elective posting based on Indonesia’s local wisdom could be one of the options. Therefore, we want to share the lesson learned from a collaborative elective posting between three faculty of medicine in Indonesia that can be a model for other medical institutions in sharing resources for learning.Aims: This case study aims to describe the implementation and lessons learned from an elective posting program.Case discussion: The collaborative elective posting is the elective posting module developed by three medical institutions from three different areas based on each of their local wisdom. Each institution recruits two pre-clinical students from another institution to join the module together with a group of students from the original institution. The module is four weeks long and worth three credits. Various learning methods, including lectures, small group discussions, and field studies, were used in each module. The goal of each module was assessed by portfolio, final report, and final writing test. At the end of the module, a self-administered questionnaire was used to assess student and team satisfaction. All students (100%) enjoyed the module and received excellent final grades ranging from A- to A; however, there were some difficulties in the module management, including scheduling and facilities.Conclusion: The collaborative elective posting is a learning innovation that can be utilized to improve medical education efficiency and efficacy.